Penerapan Senam Dismenore Pada Remaja Putri di Kecamatan Sukarami - Putu Mae Lovenya; MK Fitriani Fruitasari; Novita Anggraini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Dysmenorrhea is a gynecological complaint resulting from an imbalance of the hormone progesterone in the blood, resulting in pain. The impact of menstrual pain is very diverse, including young women being unable to walk, having difficulty sleeping, being in a bad mood, losing concentration in doing something, and so on. Gymnastics is a relaxation technique for experiencing dysmenorrhea. To find out nursing care for adolescents with reproductive disorders, dysmenorrhea, the design used in this scientific report is a case study. This case study results from the application of Evidence Based Practice (EBP), client K experienced moderate dysmenorrhea pain on a scale of 4 after being given the intervention, decreasing to mild pain on a scale of 2, client R experienced mild dysmenorrhea pain with a pain scale of 3 after being given the intervention, decreasing to mild pain on a scale of 1 and client S experienced mild dysmenorrhea pain with a pain level of 3 after being given the intervention, decreasing to no pain on a scale of 0. Applying Evidence Based Practice (EBP) it can be concluded that dysmenorrhea exercises can reduce the dysmenorrhea pain experienced by young women during menstruation.